Thursday

November 27, 2014

November 27, 2014

Posted by **Lisa** on Tuesday, February 7, 2012 at 7:37pm.

1.) Given: a→b

a

Conclusion: b

2.) Given: a˅b

~b

Conclusion: ~a

3.) Given: a→b

~b

Conclusion: ~a

4.) Given: a→b

b→~c

Conclusion: a→~c

- Geometry (Logic) -
**Steve**, Wednesday, February 8, 2012 at 5:10am#2 is not an argument, since there is no implication.

**Answer this Question**

**Related Questions**

Chemistry - Use the data given below to construct a Born - Haber cycle to ...

Chemistry - Given the following hypothetical equations, 2A + B → 3C + 2D...

Philosophy - HELP - How would you construct a proof to show that the following ...

Philosophy - How would you construct a proof to show that the following ...

phi103 - 1. A conditional sentence with a false antecedent is always (Points : ...

Chemistry - I think these I know how to do ....just want someone to check..still...

Informal Logic-Pls chk ans - The sentence "P → Q" is read as (3) P or Q P ...

add maths - Function f and g are defined by f:x→4-x and g:x→px^2+q ...

Logic - The sentence "P → Q" is read as (3) P or Q P and Q If P then Q Q ...

maths - A sequence is defined by un = 2×(−0.5)n + 3 (n = 1,2,3, . . .). ...